1993
DOI: 10.1037/0033-295x.100.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Four systems for emotion activation: Cognitive and noncognitive processes.

Abstract: The significant role of emotions in evolution and adaptation suggests that there must be more than 1 mechanism for generating them. Nevertheless, much of current emotion theory focuses on cognitive processes (appraisal, attribution, and construal) as the sole, or primary, means of eliciting emotions. As an alternative to this position, the present model describes 4 types of emotion-activating systems, 3 of which involve noncognitive information processing. From an evolutionary-developmental perspective, the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
374
1
39

Year Published

1995
1995
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 604 publications
(434 citation statements)
references
References 176 publications
8
374
1
39
Order By: Relevance
“…Emotional experiences result from emotion-related muscular actions. James's basic thesis has been taken up in recent years by a number of investigators, most notably by Tomkins (1962Tomkins ( -1963, Izard (1971Izard ( , 1993, Ekman (1984Ekman ( , 1993, and Laird (e.g., Laird & Bresler, 1992). Although these researchers typically devoted most of their attention to the emotion-arousing effects of facial expressions, some of them (e.g., Duclos et al, 1989;Riskind & Gotay, 1982) subsequently extended their research to the consequences of muscular movements in other parts of the body.…”
Section: Effects Of Anger-related Muscular Movementsmentioning
confidence: 99%
See 3 more Smart Citations
“…Emotional experiences result from emotion-related muscular actions. James's basic thesis has been taken up in recent years by a number of investigators, most notably by Tomkins (1962Tomkins ( -1963, Izard (1971Izard ( , 1993, Ekman (1984Ekman ( , 1993, and Laird (e.g., Laird & Bresler, 1992). Although these researchers typically devoted most of their attention to the emotion-arousing effects of facial expressions, some of them (e.g., Duclos et al, 1989;Riskind & Gotay, 1982) subsequently extended their research to the consequences of muscular movements in other parts of the body.…”
Section: Effects Of Anger-related Muscular Movementsmentioning
confidence: 99%
“…Then too, research into the conditions under which anger is aroused can also touch on the metatheoretical controversy as to whether emotions can be evoked independently of cognitions. Although we do not want to revive the now well-worn argument as to just what is involved in the concept cognition, if one adopts the relatively restricted definition favored by Izard (1993) and Zajonc 1 In their questionnaire study of some 2,900 university students on five continents, Scherer and Wallbott (1994) found that, for the emotions they investigated, the similarities in reported emotion-specific feelings, physiological symptoms, and bodily expressions across countries were much greater than the variations among the countries. And they concluded that "The data reported here do not support an extreme position of cultural relativism with respect to emotional experience" (p. 324).…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Results show that even engagement and social interaction are encouraged by controllers that afford movement [26]. Izard et al [27] describes neural, sensorimotor, motivational and cognitive processes that can influence emotions. Body posture and movement can activate emotions by afferent processes.…”
Section: Motion Emotion Interaction and Experiencementioning
confidence: 99%